Correlation between Selective and Non-selective α-Blocker Drugs with Age, Prostate Volume and Different Benign Prostate Hyperplasia (BPH) Indicators - Islam Abdul Rasool Hashim (Journal of Global Pharma Technology, 2016)
Objective: This study aimed to evaluating  the correlation between(age, prostate size) and different BPH indicators such as ( PSA , IPSS , testosterone , estrogen ,Testosterone/Estrogen {T/E} ratio ) among two groups (one treated with selective and  another treated with non-selective α-blocker drugs) and untreated group. Methods: The study is a randomized control clinical trial carried out in Urology department during the period from September /2018 to May /2019.The study was based on 60 cases of symptomatic Benign Prostatic Hyperplasia, 30 patients treated with selective α-blocker drug (tamsulosin) and 30patients treated with non-selective α-blocker drug (alfuzosin) and 30 cases of newly diagnosed patients with BPH but did not take treatment for BPH disease, the range of their age was between (50-90). The variables age, prostate size, PSA, IPSS, testosterone, estrogen, T/E ratio were examined and appropriate statistical tests were employed for data analysis. Results: The results showed that there was a significant difference in correlation between age with IPSS and between age with  testosterone (p≤0.05)among treated and untreated groups and also showed a significant difference in linear  correlation between PSA ,Testosterone, Estrogen indicators levels and the  prostate size (p≤0.05) among treated and untreated groups  Conclusion: In men with biopsy-proven BPH , both International Prostate Symptom Score IPSS and testosterone increased and altering with ageing. Prostate size demonstrated significant positive correlations with Prostate Specific Antigen PSA, Testosterone, Estrogen among treated and untreated groups in this study.Keywords: BPH, Testosterone, Estrogen, PSA, IPSS, Tamsulosin, Alfuzosin.